2021
DOI: 10.1016/j.hest.2021.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic peduncular, cavernous bleeding following SARS-CoV-2 vaccination induced immune thrombocytopenia

Abstract: Therapy-responsive immune thrombocytopenia and anemia shortly after the second dose of an mRNA-based SARS-CoV-2 vaccine, which was complicated by symptomatic bleeding within a pre-existing brainstem cavernoma, has not been reported. The patient is a 68yo male who experienced gait disturbance and hypoesthesia of the left face and left upper extremity two days after the second dose of the mRNA-based SARS-CoV-2 vaccine BNT162b2 (Tozinameran). Clinical neurologic exam revealed hypoesthesia of the left f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…There are 16 cases of ITP, 12 cases of TTP reactivation, 11 cases of suspected intracerebral hemorrhage (ICH), 6 cases of cerebral venous sinus thrombosis, 1 case of pulmonary embolism, 1 case of renal thrombotic microangiopathy, a case of ST-elevation myocardial infarction (STEMI), 1 case of stroke, 1 case of central retinal artery occlusion, and a case of lower limb DVT associated with BNT162b2( Fig. 1 ) [ [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] ]. The STEMI reported in an elderly gentleman with multiple cardiovascular and pro-thrombotic risk factors 30mins post first dose of BNT162b2 is attributed to vaccination-induced “Kounis syndrome” or allergic myocardial infarction likely secondary to mast cell activation from an allergic or anaphylactoid reaction [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are 16 cases of ITP, 12 cases of TTP reactivation, 11 cases of suspected intracerebral hemorrhage (ICH), 6 cases of cerebral venous sinus thrombosis, 1 case of pulmonary embolism, 1 case of renal thrombotic microangiopathy, a case of ST-elevation myocardial infarction (STEMI), 1 case of stroke, 1 case of central retinal artery occlusion, and a case of lower limb DVT associated with BNT162b2( Fig. 1 ) [ [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] ]. The STEMI reported in an elderly gentleman with multiple cardiovascular and pro-thrombotic risk factors 30mins post first dose of BNT162b2 is attributed to vaccination-induced “Kounis syndrome” or allergic myocardial infarction likely secondary to mast cell activation from an allergic or anaphylactoid reaction [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finsterer and Redzic [ 4 ] reported a brainstem cavernous hemangioma hemorrhage that occurred 2 days after the second dose of the mRNA COVID-19 vaccine, the pre-existing vascular malformation might have caused bleeding due to thrombocytopenia or platelet dysfunction after vaccination. Also, Gessler et al [ 5 ] reported 3 cases of intracerebral hemorrhage with thrombocytopenia after vaccination with Oxford/AstraZeneca and Janssen vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated immune responses in COVID cases can contribute to the production of immune-mediated processes via activation of different inflammation-related cells and production of cytokines, resulting in a wide range of clinical manifestations, such as Guillain-Barré Syndrome (GBS) [8] . Also, those processes can lead to ICB as a result of dysfunctional thrombocytes [9] . In our case [2] the patient D-dimer was high (14 μg/ml) with thrombocytopenia which improved through hospital stay.…”
mentioning
confidence: 99%